2003
DOI: 10.1159/000069082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mitoxantrone on Multiple Sclerosis Patients’ Lymphocyte Subpopulations and Production of Immunoglobulin, TNF-alpha and IL-10

Abstract: We designed this longitudinal study to clarify the short- and long-term effects of mitoxantrone on the immune system in a subgroup of multiple sclerosis patients treated at our centre. After 14 days we found a highly significant sustained reduction of leucocytes, primarily affecting neutrophils and most lymphocyte subsets except for naive and activated T lymphocytes. The CD4/CD8 ratio and serum immmunoglobulin levels were not affected. Furthermore, whole blood-stimulated mononuclear cell IL-10 production showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 14 publications
3
20
0
2
Order By: Relevance
“…The main difference of our study compared to previous investigations is that we performed an in vitro study over 6 months, while others focused on short-term effects (from 1 h to 14 days) [8, 9]. Our longitudinal data showed that MX led to a selective decrease in B cells that persists after the first treatment cycle.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The main difference of our study compared to previous investigations is that we performed an in vitro study over 6 months, while others focused on short-term effects (from 1 h to 14 days) [8, 9]. Our longitudinal data showed that MX led to a selective decrease in B cells that persists after the first treatment cycle.…”
Section: Discussionmentioning
confidence: 84%
“…Despite its widespread use, the immunological effects of MX are not fully understood. Ex vivo analyses in MS patients revealed that MX induces suppression of mononuclear cell proliferative responses and alterations in counts of lymphocyte subsets [8, 9], preferentially B cells. However, most studies focused on acute or short-term effects of MX, and data on the long-term immunological effects of MX are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Since TNF-α was recently found to be elevated in patients suffering from fatigue [26], a reduction in TNF-α levels could hypothetically lead to reduction in fatigue. However, such an effect on TNF-α is not restricted to azathioprine alone and findings concerning this issue are difficult to interpret [27,28,29,30]. Due to methodological limitations (i.e.size of the patient sample), our statistical model is not powered adequately to analyze discrepancies between all the different agents but to compare the level of fatigue in patients treated with immune-modulating drugs vs. immunosuppressive drugs vs. untreated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mitoxantrone (MX) acts as an immunosupressive agent which alters B and T lymphocytes responses to central nervous system (CNS) antigens, and through this process it seems to avoid axonal lesion and macrophages mediated demyelination [1][2][3][4][5][6][7][8][9]13,19 . After 14 days, white blood cells counting is lowered at a significant level, firstly affecting neutrophils and the majority of lymphocytes, excepting Th 0 and activated T cells 14 . It can be administered in kidney failure or chronic pyelitis patients, diseases that might occur in MS patients, since it is preferrably eliminated through the biliary tract.…”
Section: Mitoxantrone Hydrochloride (Novantronementioning
confidence: 99%